The O‐methyltransferase gene MdoOMT1 is required for biosynthesis of methylated phenylpropenes in ripe apple fruit. (20th May 2015) - Yauk, Yar‐Khing; Chagné, David; Tomes, Sumathi; Matich, Adam J.; Wang, Mindy Y.; Chen, Xiuyin; Maddumage, Ratnasiri; Hunt, Martin B.; Rowan, Daryl D.; Atkinson, Ross G.
Summary: Phenylpropenes, such as eugenol and trans ‐anethole, are important aromatic compounds that determine flavour and aroma in many herbs and spices. Some apple varieties produce fruit with a highly desirable spicy/aromatic flavour that has been attributed to the production of estragole, a methylated phenylpropene. To elucidate the molecular basis for estragole production and its contribution to ripe apple flavour and aroma we characterised a segregating population from a Royal Gala (RG, estragole producer) × Granny Smith (GS, non‐producer) apple cross. Two quantitative trait loci (QTLs; accounting for 9.2 and 24.8% of the variation) on linkage group (LG) 1 and LG2 were identified that co‐located with seven candidate genes for phenylpropene O ‐methyltransferases ( MdoOMT1–7 ). Of these genes, only expression of MdoOMT1 on LG1 increased strongly with ethylene and could be correlated with increasing estragole production in ripening RG fruit. Transient over‐expression in tobacco showed that MdoOMT1 utilised a range of phenylpropene substrates and catalysed the conversion of chavicol to estragole. Royal Gala carried two alleles ( MdoOMT1a, MdoOMT1b ) whilst GS appeared to be homozygous for MdoOMT1b . MdoOMT1a showed a higher affinity and catalytic efficiency towards chavicol than MdoOMT1b, which could account for the phenotypic variation at the LG1 QTL. Multiple transgenic RG lines with reduced MdoOMT1 expression produced lower levels of methylated phenylpropenes, including estragole and methyleugenol. Differences in fruit aroma could be perceived in these fruit, compared with controls, by sensory analysis. Together these results indicate that MdoOMT1 is required for the production of methylated phenylpropenes in apple and that phenylpropenes including estragole may contribute to ripe apple fruit aroma. Significance Statement: Phenylpropenes such as eugenol, anethole and estragole have been shown to contribute to the aromas of a range of herbs and flowers, however, their contribution to fruit flavour and aroma has not been resolved. Our results indicate that the O ‐methyltransferase MdoOMT1 is required for biosynthesis of methylated phenylpropenes in ripe apple fruit and that phenylpropenes including estragole may contribute to ripe apple aroma.